CLINICAL AND INSTRUMENTAL PREDICTORS OF SURVIVAL IN PATIENTS WITH CLINICALLY MANIFESTED LEFT VENTRICU-LAR SYSTOLIC DYSFUNCTION - Ustimenko, H.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The aim of the present study was to investigate the dependence of survival from  clinical and echocardiographic   predictors  in patients  with clinically manifested chronic heart failure (CHF) with left ventricular (LV) systolic dysfunction. The database represents 225 clinically manifested CHF patients with impaired ejection fraction (EF£40%) LV systolic function. NYHA status II-IV; ischemic or/and hypertensive - 105 patients, non - ischemic - 120 patients. Chronic atrial  fibrillation had 87 patients. Definition of survival was performed using Kaplan-Meier method and the method of life tables.  All the calculations were made using the «STATISTICA for Windows. Release 5.1». During 1, 3 and 5th years survived accordingly 86%, 55% and 33% patients. Cumulative survival in patients  with clinically manifested CHF with left ventricular systolic dysfunction during 10 years reflects dependence from end-diastolic index, EF, end-systolic volume, relative wall thickness, end-diastolic volume (EDV),  myocardial mass to EDV ratio, systolic blood pressure and NYHA class of CHF and doesn’t reflect dependence from the aetiology of CHF, left atria dimension, LV stroke index, LV mass index and   presence of chronic atrial  fibrillation.